2017
DOI: 10.1094/cchem-06-16-0166-r
|View full text |Cite
|
Sign up to set email alerts
|

Cooking Quality, Antioxidant Properties, and Starch Digestibility of Wheat Noodles Substituted with Extruded Brown Rice Flour

Abstract: Cereal Chem. 94(3):464-470The effect of extruded brown rice flour (EBR) contents (0-50%) on antioxidant activity, phenolics, in vitro digestibility, color, and cooking quality of noodles containing mixtures of wheat and EBR was investigated. The antioxidant activity and phenolic content increased, especially ferulic and coumaric acids in bound forms, whereas the in vitro glycemic index, optimal cooking time, water absorption, hardness, and color were diminished in noodles with the addition of EBR; cooking loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…However, a heat‐moisture treatment of BR flour increased the resistant starch content and decreased the rapidly digestible starch content in Korean rice‐based cakes (Kim, Oh, & Chung, ). Furthermore, the in vitro starch digestibility in noodles was found to be decreased as the addition percentage of extruded BR flour to wheat flour increased (Wu, Tan et al., ). Therefore, digestibility of BR‐based food products can be controlled by choosing an appropriate processing method and optimization of processing conditions.…”
Section: Digestibilitymentioning
confidence: 99%
See 3 more Smart Citations
“…However, a heat‐moisture treatment of BR flour increased the resistant starch content and decreased the rapidly digestible starch content in Korean rice‐based cakes (Kim, Oh, & Chung, ). Furthermore, the in vitro starch digestibility in noodles was found to be decreased as the addition percentage of extruded BR flour to wheat flour increased (Wu, Tan et al., ). Therefore, digestibility of BR‐based food products can be controlled by choosing an appropriate processing method and optimization of processing conditions.…”
Section: Digestibilitymentioning
confidence: 99%
“…Because of its high nutritional value and potential health benefits, several studies were performed for the purpose of developing BR‐based noodles or pasta products (Table ). BR‐based noodles were developed by partial replacement of wheat flour with heat‐moisture treated (HMT) and germinated BR flour (Chung, Cho, & Lim, ); untreated BR flour (Kim et al., ); or extruded BR flour (Wu, Tan et al., ). Also, noodles were prepared from BR only as a single component and compared with that prepared from WR (Baek & Lee, ).…”
Section: Development Of Food Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…This process promotes the formation of new and effective starch structures to replace gluten networks in products, which could improve the texture of dough and the sensory quality of noodle (Yang et al, ). It has been reported that addition of extruded finger millet (Patil et al, ), wheat bran (Gómez, Jiménez, Ruiz, & Oliete, ), wheat germ (Gómez, González, & Oliete, ), wheat flour (Martínez et al, ), sorghum (Jafari, Koocheki, & Milani, ), and brown rice (Wu et al, ) to wheat flour could improve the elasticity and toughness of the composite dough, and form compact bread and noodle structure. However, extrusion of mung bean flour had not been systematically and thoroughly studied, and there were few reports about the extruded mung bean–wheat composite flour to make noodles regarded as the staple food product.…”
Section: Introductionmentioning
confidence: 99%